A Cross-Sectional Survey of Knowledge of Skin Cancer in Saudi Arabia - Hend Al-Atif (Mattioli1885, 2021)
Background: Skin cancer has become one of the world's leading health problems, and incidence rates are on the rise. The leading causes of skin cancer are sun exposure, family history and sunburn, and the most agreed-upon preventative behaviors are sunscreen application and sun avoidance. Objectives: This study assessed the knowledge of the causes of skin cancer and awareness of preventative measures in Saudi Arabia. Methods: A cross-sectional study was conducted among 529 participants in a WhatsApp group over 3 months. Consenting participants completed a validated, 18-item questionnaire. Results: Of 529 total participants, nearly 55% of participants reported an awareness of skin cancer, 35% understood its metastasis and 55.1% knew about its spread. However, 44% of participants were unaware of the different types of the disease. Social media was reported to be the most common source of information. The majority of participants were able to identify symptoms of skin cancer and had knowledge of risk factors. Most participants understood proper preventative measures, and reported that they use sunscreen regularly. Conclusions: The general knowledge of skin cancer in Saudi Arabia is not high but is increasing. However, sun-protective behaviors are lacking, despite the population's knowledge of the benefits. Awareness campaigns and incentive programs may encourage better preventative behavior. Future studies should explore participants' awareness of more specific aspects of skin cancer using a more diverse and extensive population sample.